2020
DOI: 10.1038/s41377-020-00395-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep-blue organic light-emitting diodes based on a doublet d–f transition cerium(III) complex with 100% exciton utilization efficiency

Abstract: Compared to red and green organic light-emitting diodes (OLEDs), blue OLEDs are still the bottleneck due to the lack of efficient emitters with simultaneous high exciton utilization efficiency (EUE) and short excited-state lifetime. Different from the fluorescence, phosphorescence, thermally activated delayed fluorescence (TADF), and organic radical materials traditionally used in OLEDs, we demonstrate herein a new type of emitter, cerium(III) complex Ce-1 with spin-allowed and parity-allowed d–f transition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…We note that such a short excited-state lifetime potentially enhances luminous efficiency and reduces efficiency roll-off and device degradation . More importantly, the Ce element is earth-abundant and nontoxic, and the Earth’s crust abundance of Ce is 0.006 wt %, which is comparable with that of Pb (0.010 wt %) and even higher than that of Cu (0.005 wt %) …”
mentioning
confidence: 82%
See 1 more Smart Citation
“…We note that such a short excited-state lifetime potentially enhances luminous efficiency and reduces efficiency roll-off and device degradation . More importantly, the Ce element is earth-abundant and nontoxic, and the Earth’s crust abundance of Ce is 0.006 wt %, which is comparable with that of Pb (0.010 wt %) and even higher than that of Cu (0.005 wt %) …”
mentioning
confidence: 82%
“…19 More importantly, the Ce element is earth-abundant and nontoxic, and the Earth's crust abundance of Ce is 0.006 wt %, which is comparable with that of Pb (0.010 wt %) and even higher than that of Cu (0.005 wt %). 20 Based on all these advantages, we may expect excellent optoelectronic properties of Ce 3+ -based perovskites or perovskite derivatives; however, they have never been investigated for electrically driven LEDs applications so far. To ensure better thermal stability, we focus on the Cs−Ce−Br ternary system with an all-inorganic nature.…”
mentioning
confidence: 99%
“…Organic light-emitting diodes (OLEDs) have developed rapidly over the past few decades. To achieve high efficiency, fluorescence, phosphorescence, thermally activated delayed fluorescence, hybridized local and charge-transfer excited-state fluorescence, , radical-based luminescence, and d-f transition-based luminescence have been developed sequentially. As a new type of emitter in OLEDs, d-f transition Ce­(III) complexes have significant advantages, such as short excited-state lifetimes in the range of nanoseconds, ,, up to a 100% theoretical exciton utilization efficiency due to the spin- and parity- allowed d-f transitions, , and tunable emission colors, since the 5d energy levels are sensitive to the external environment. …”
Section: Introductionmentioning
confidence: 99%
“…Despite all these satisfying advantages, photoluminescence (PL) research on d-f transition Ce­(III) complexes is limited. Most reported Ce­(III) complexes are nonemissive due to the luminescence quenching by ligands and solvent molecules, and the electroluminescence (EL) studies on Ce­(III) complexes are more rare. , Recently, we reported two novel Ce­(III) complexes Ce-1 and Ce-2 based on the hydrotris­(3,5-dimethylpyrazolyl)­borate (Tp Me2 ) ligand. It is found that the deep blue emissive Ce-1 showed an average external quantum efficiency (EQE) of 12.4%, while the sky blue emissive Ce-2 showed a maximum EQE up to 20.8% in their prototype OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In 2020, a new kind of OLEDs with doublet emission was reported by Liu et al, in which a novel rare earth metal cerium (III) complex which possesses a doublet blue emission from the d-f transition was used as the emitter. [18] A follow-up work was carried out and a maximum external quantum efficiency (EQE) of 20.8% was obtained. [19] Apart from radicals and cerium (III) complexes, earth-abundant transition-metal complexes with low-spin d 5 electronic structure may have the doublet metal-to-ligand charge transfer ( [Fe(phtmeimb) 2 ]PF 6 , [21] where phtmeimb stands for [phenyl(tris(3-methylimidazol-1-ylidene))borate] -.…”
Section: Introductionmentioning
confidence: 99%